Literatur Review: Model Evaluasi CIPP pada Program Bimbingan Konseling Sekolah - Muslimin, Rika Rahayu; Syamsudduha, St. (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Assessment of counseling guidance programs in schools is very important to ensure that the program can run well and have a positive impact on the development of students. One evaluation model that is often used in the assessment of counseling guidance programs is the CIPP (Context, Input, Process and Product) model developed by Stufflebeam. This study aims to review and compare various studies that have applied the CIPP model in evaluating school counseling guidance programs. The research method used is a literature review by first analyzing its application then comparing several journals that discuss counseling guidance programs using the CIPP evaluation model, drawing conclusions and providing recommendations for future research or practice. Data collection is done by collecting supporting literature from books and also research journals from various sources. The results showed that the three studies that used the CIPP model on counseling programs showed that despite facing different challenges, this model was effective in program evaluation. In SMA Negeri Tegal Regency, the implementation of the CIPP model went well thanks to the supportive background of the teachers. At SMK Penerbangan PBD Medan, despite limited resources and facilities, the program still had a positive impact. Meanwhile, at SMKN 34 Jakarta, most aspects of the program were rated as good, but improvements were still needed in terms of teacher coordination and parental understanding. Overall, the CIPP model provides a comprehensive picture for the improvement of counseling guidance programs.